Baalbek, Libanon. Die Entwicklung der Stadt vom 8. Jahrtausend v. Chr. bis in die Gegenwart - van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
Between 2001 and 2011 a comprehensive research project was carried out in Baalbek for the documentation of excavated but not yet published archaeological architectural remains and findings. It aimed at investigating the urban development of the town from its beginning until present. The results of this project are in preparation for publication now. In the year 2012 additional excavations were undertaken at the pre-Roman settlement. For the first time, detailed pottery sequences of the Middle Bronze Age and more exact datings are developed for the Northern Beqaa valley.